State of the world 2021: autocratization changing its nature?. Issue 6 (18th August 2022) - Boese, Vanessa A.; Lundstedt, Martin; Morrison, Kelly; Sato, Yuko; Lindberg, Staffan I.
ABSTRACT: This article analyses the state of democracy around the world in 2021. The level of democracy enjoyed by the average global citizen in 2021 was down to 1989 levels. In 2021, autocracies were on the rise, harbouring 70% of the world population, or 5.4 billion people. There was also a record number of countries autocratizing in 2021: 33 countries, home to 36% of the global population. In recent years, the EU seems to be facing its own wave of autocratization, with 20% of its members autocratizing over the last decade. In addition to the continued downturn in global democracy, this article documents several signs that autocratization is changing in nature. Polarization increased substantially and signiﬁcantly in 40 countries between 2011 and 2021, and our analysis indicates that polarization increasingly damages democracy especially recently and under anti-pluralist governments. Over the past decade, the data also shows that autocratic governments more frequently used misinformation to shape domestic and international opinion. Finally, with ﬁve military coups and one self-coup, 2021 featured an unprecedented increase in coups for this century. These coups contributed to the uptick in the number of closed autocracies in 2021 and seem to signal a shift toward emboldened autocratic actors.